Diamond Open Access - a robust, accessible and federated network for journals (PUBMET, 2023)
While Diamond Open Access is widely considered the most progressive publishing form for Open Access journals, these journals face various challenges including (technological) standardisation, ensuring sustainability for journals, and juggling a broad set of workflows while depending largely on voluntary work.The CRAFT-OA project (Creating a Robust Accessible Federated Technology for Open Access) aims to help standardise Diamond Open Access journals by offering technological innovations available to all Diamond Open Access journals. In cooperation with the DIAMAS project, CRAFT-OA will foster a community of practice, further enhancing Diamond Open Access publishing by uniting the scholarly community behind common goals.The proposed poster will include an overview of the key objectives and phases of the project as well as a section dedicated to explaining how the project’s results will support diamond OA publishing and be made available via the capacity centre prepared jointly with the DIAMAS project. Specifically, it will explain how the results of DIAMAS and CRAFT-OA complement each other in that regard by providing all information, best practice guidelines, workflows and training materials relating to Diamond Open Access in one place.
Keywords: Diamond Open Access publishing; scholarly communication